Compression behaviour of quasicrystal/Al composite with powder mixture driven layered microstructure prepared by selective laser melting. (September 2020) - Lu, J.L.; Lin, X.; Liao, H.L.; Kang, N.; Huang, W.D.; Coddet, C.
Graphical abstract: Highlights: The compressive properties of SLM-processed QC/Al composite are anisotropic. Layered microstructure caused by local concentration variation of QC is observed. The layered microstructure results in anisotropic crack propagation mechanisms. Abstract: The effect of powder mixture on the mechanical properties of in-situ SLM processed Al-Fe-Cr quasicrystal (QC) reinforced α-Al matrix composite was investigated in this work. The results show that the microstructure is inhomogeneous with non-uniformly distributed QC particles in the melt pool from non-equilibrium solidification during SLM, which results in a special anisotropic compression behavior. In details, the microstructure consists of micron-sized columnar grains growing from the melt pool boundary to the melt pool centre, with width of 3 μm on average. Due to the higher density of QC than Al, the QC particles tend to gather at melt pool boundaries under Marangoni convection to form QC-rich regions and QC-poor regions in the melt pool, resulting in layered microstructure. Both the yield strength and the compressive strength along the building direction, with values of 501 MPa and 1159 MPa, respectively, are higher than those perpendicular one. This compressive properties anisotropy is attributed to the anisotropic crack propagation mechanisms when loaded in different directions, which results from the inhomogeneous microstructure within the melt pool.